Чи обтяжує покарання за незаконне проведення аборту вагітність потерпілої? - Павленко, І.В. (Альманах права, 2012)
Стаття присвячена розгляду питання про обтяжуючі обставини при незаконному проведенні аборту в Україні. Так, зокрема, аналізується питання про те, чи можна визнавати стан вагітності потерпілої як обставину, що обтяжує покарання згідно ст. 134 КК України. Статья посвящена рассмотрению вопроса об отягчающих обстоятельствах при незаконном проведении аборта в Украине. В частности, анализируется вопрос о том, можно ли считать состояние беременности потерпевшей в качестве обстоятельства, которое отягчает наказание согласно ст. 134 УК Украины. The article examines the possibility to count the pregnancy of victim as aggravator of illegal abortion. This issue was aroused in criminal cases legal practice of Ukraine in respect of Article 134 of the Criminal code of Ukraine. Consequently by basis for writing of the article and there are materials of these criminal cases. In addition, the article gives different scientific points of view regarding aggravator, in particular, it was mentioned the view of N.F. Kuznecova, S.S. Gaskin, L.L. Kruglikov. The article examines the division of aggravating circumstances on the following: foreseen by General part and by Special part of the Criminal code of Ukraine. Pursuant to the above mentioned the author divided into groups the aggravator as state of pregnancy of victim at the feasance of illegal abortion and in general aggravator in the context of item 134 the Criminal code of Ukraine. An issue is separately affected by influence of aggravator on foundation and pre-condition of criminal responsibility in general. As a conclusion leadthrough of abortion is illegal and foresees the presence of pregnancy. Consequently, pregnancy is a structural sign of crime, responsibility for which is foreseen by Art. 134 of the Criminal code of Ukraine. The author of the article comes to the final conclusion that the pregnancy of victim in context of illegal leadthrough of abortion is not and can not be a circumstance which burdens punishment.